The Robotarium: A Remotely-Accessible, Multi-Robot Testbed for Control Research and Education - Wilson, Sean; Egerstedt, Magnus (IEEE Open Journal of Control Systems, 2023)
In robotic research and education, the cost in terms of money, expertise, and time required to instantiate and maintain robotic testbeds can prevent researchers and educators from including hardware based experimentation in their laboratories and classrooms. This results in robotic algorithms often being validated by low-fidelity simulation due to the complexity and computational demand required by high-fidelity simulators. Unfortunately, these simulation environments often neglect real world complexities, such as wheel slip, actuator dynamics, computation time, communication delays, and sensor noise. The Robotarium provides a solution to these problems by providing a state-of-the-art, multi-robot research facility to everyone around the world free of charge for academic and educational purposes. This paper discusses the remote usage of the testbed since its opening in 2017, details the testbeds design, and provides a brief tutorial on how to use it.